2015
DOI: 10.1586/1744666x.2015.1090313
|View full text |Cite
|
Sign up to set email alerts
|

Biosimilars for the management of rheumatoid arthritis: economic considerations

Abstract: Biologic drugs have proved highly effective for the treatment of immune-mediated inflammatory diseases such as rheumatoid arthritis (RA). These drugs are often considered cost-effective for well-defined RA patient populations not responding adequately to conventional treatment, but are used first-line relatively rarely, partly due to high costs. Furthermore, not all clinically eligible patients can access biologics even as second-line therapy. Recently, there has been a rise in interest in 'biosimilar' drugs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 54 publications
(33 reference statements)
1
53
0
6
Order By: Relevance
“…BIA analyses are limited in the literature, both in general [34] and with respect to second-generation biosimilars [12]; therefore, the present study represents a valuable addition to the current knowledge base. In 2014, a systematic literature review identified a total of 17 EU BIA publications across all therapy areas [71].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BIA analyses are limited in the literature, both in general [34] and with respect to second-generation biosimilars [12]; therefore, the present study represents a valuable addition to the current knowledge base. In 2014, a systematic literature review identified a total of 17 EU BIA publications across all therapy areas [71].…”
Section: Discussionmentioning
confidence: 99%
“…All of these diseases have significant financial impacts on global healthcare systems. For example, RA is a chronic, progressive disease associated with significant direct and indirect costs to society [12, 13]. As the population ages, RA becomes an increasing burden globally.…”
Section: Introductionmentioning
confidence: 99%
“…After the expiry of the patent protection of originator biological molecules, their less costly alternatives, biosimilars can enter the market with the promise of savings in the healthcare budget or enabling better patient access to biological treatment (Gulácsi et al 2015). Biosimilars are developed to be similar to already authorized reference biological medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews have emphasised potential cost savings from the use of biosimilars,16 17 and some budget impact analyses were performed to quantify these cost reductions. Haustein et al showed that the use of biosimilars in Europe was expected to result in overall cost savings of €11.8 billion to €33.4 billion between 2007 and 2020, and of €2.9 billion to €6.3 billion in France only 18.…”
Section: Introductionmentioning
confidence: 99%